Policy options for obesity in Europe : a comparison of public health specialists with other stakeholders (2008)
ABSTRACT: Objective: To explore policy options that public health specialists (PHS) consider appropriate for combating obesity in Europe, and compare their preferences with those of other stakeholders (non-PHS). Design: Structured interviews using multicriteria mapping, a computer-based, decision-support tool. Setting: Nine European countries. Subjects: A total of 189 stakeholders. Twenty-seven interviewees were PHS and non-PHS included food, sports and health sectors. Measurements: A four-step approach was taken, i.e. selecting options, defining criteria, scoring options quantitatively and weighting the criteria to provide overall rankings of options. Interviews were recorded and transcribed to yield qualitative data. Results: The PHS concur with other stakeholders interviewed, as all emphasised the importance of educational initiatives in combating obesity, followed by policies to improve community sports facilities, introduce mandatory food labelling and controlling food and drink advertising. Further analyses revealed several significant differences. The non-PHS from the private sector ranked institutional reforms favourably; the PHS from non-Mediterranean countries supported the option of medicines to prevent obesity; and those PHS from Mediterranean countries endorsed the use of activity monitoring devices such as pedometers. As far as appraisal criteria were concerned, PHS considered efficacy and the economic impact on the public sector to be the most important. Conclusion: There is clear consensus among PHS and other stakeholders concerning the need for a package of policy options, which suggests that European-wide implementation could be successful. However, it would be advisable to avoid more contentious policy options such as taxation until future changes in public opinion.